Adipocytokines in early rheumatoid arthritis: relationship to pro- and anti-inflammatory markers - L. V. Kondratyeva; T. V. Popkova; Yu. N. Gorbunova (Научно-практическая ревматология, 2019)
Objective: to clarify the relationship of adiponectin and leptin to the signs of disease activity and the levels of pro- and anti-inflammatory cytokines in patients with early rheumatoid arthritis (RA).Subjects and methods. The investigation enrolled 27 RA patients who met the 2010 ACR/EULAR classification criteria and had never received glucocorticoids (GCs) or disease-modifying antirheumatic drugs. The median age of the patients was 56 [46; 64] years; the duration of the disease was 8 [6; 15] months. All the patients had moderate or high RA activity according to DAS28. The majority of the patients were seropositive for rheumatoid factor (88.9%) or anticyclic citrullinated peptide antibodies (96.3%). A control group included 30 gender-, age-, and body mass index (BMI)-matched people without inflammatory arthritis. Enzyme immunoassay was used to estimate the concentrations of adiponectin and leptin; XMAP multiplex assay was applied to measure the levels of interleukin-1β (IL-1β), IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-9, IL-10, IL-12, IL-13, IL-15, IL-17 and macrophage inflammation proteins (MIP), such as MIP-1α and MIP-1β.Results and discussion. In RA patients, adiponectin concentrations were higher (p<0.001) and leptin levels and leptin/adiponectin (L/A) ratios were lower than those in the controls (p=0.04 and p<0.001, respectively). In RA, there were direct correlations of leptin levels with concentration of IL-17 (r=0.4; p=0.03), IL-4 (r=0.39; p=0.04) and erythrocyte sedimentation rate (ESR) (r=0.3; p=0.05), as well as relationships of L/A ratios to ESR (r=0.38; p=0.05) and the levels of CRP (r=0.4; p=0.04) and MIP-1β (r=0.55; p=0.03). An increase in adiponectin concentrations was associated with a decrease in MIP-1β levels (r=-0.63; p<0.01). In patients with BMI ≥25 kg/m2, leptin concentrations were comparable in RA patients and controls (p=0.1); the differences in adiponectin levels and L/A ratios remained in both cases (p<0.001). This subgroup of patients with RA showed significant correlations between leptin and IL-17 levels (r=0.52; p=0.03), adiponectin and MIP-1β concentrations (r=-0.59; p=0.01), L/A ratios and MIP-1β levels (r=0.55; p=0.02).Conclusion. In early RA, there was a lower leptin synthesis and a higher adiponectin production. The correlations between the levels of adipocytokines, IL-17, and MIP1β, on the one hand, suggest that adipose tissue has an impact on systemic inflammation and, on the other, confirm that proinflammatory cytokines are involved in the development of insulin resistance and obesity.